THE INFLUENCE OF PROMOTION STRATEGY AND BRAND IMAGE ON PURCHASE DECISIONS FOR COMPASS COLLABORATION SHOES IN CIPUTAT DISTRICT, SOUTH TANGERANG - Siti Hanah (Transpublika Publisher, 2024)
This study investigates the influence of promotion strategy and brand image on consumer purchase decisions for Compass collaboration shoes in the Ciputat District, South Tangerang. As the Indonesian footwear market becomes increasingly competitive, effective promotional activities and strong brand positioning are essential for shaping consumer preferences. Using a quantitative research approach, data were collected through structured questionnaires distributed to consumers who have purchased or shown interest in Compass collaboration products. The analysis was conducted using multiple regression to determine the direct effects of promotion strategy and brand image on purchase decisions. The results indicate that both promotion strategy and brand image significantly and positively influence consumer purchasing decisions. Promotion strategies such as digital marketing, influencer endorsements, and limited-edition product releases were found to enhance consumer awareness and encourage purchase intention. Likewise, a strong brand image, characterized by product uniqueness, cultural relevance, and emotional connection, plays a critical role in driving purchasing behavior. These findings highlight the importance for brands to integrate creative promotional efforts with consistent brand identity to effectively capture market attention. The study provides managerial insights for footwear brands seeking to strengthen market competitiveness through strategic marketing initiatives.